Structural correlates of skilled performance on a motor sequence task - Steele, Christopher J.; Scholz, Jan; Douaud, Gwenaëlle; Johansen-berg, Heidi; Penhune, Virginia B. (Frontiers in Human Neuroscience, 2012)
The brain regions functionally engaged in motor sequence performance are well established, but the structural characteristics of these regions and the fibre pathways involved have been less well studied. In addition, relatively few studies have combined multiple magnetic resonance imaging (MRI) and behavioural performance measures in the same sample. Therefore, the current study used diffusion tensor imaging, probabilistic tractography, and voxel-based morphometry to determine the structural correlates of skilled motor performance. Further, we compared these findings with fMRI results in the same sample. We correlated final performance and rate of improvement measures on a temporal motor sequence task with skeletonised fractional anisotropy (FA) and whole brain grey matter (GM) volume. Final synchronisation performance was negatively correlated with FA in white matter underlying bilateral sensorimotor cortex – an effect that was mediated by a positive correlation with radial diffusivity. Multi-fibre tractography indicated that this region contained crossing fibres from the corticospinal tract and superior longitudinal fasciculus (SLF). The identified SLF pathway linked parietal and auditory cortical regions that have been shown to be functionally engaged in this task. Thus, we hypothesise that enhanced synchronisation performance on this task may be related to greater fibre integrity of the SLF. Rate of improvement on synchronisation was positively correlated with GM volume in cerebellar lobules HVI and V – regions that showed training-related decreases in activity in the same sample. Taken together, our results link individual differences in brain structure and function to motor sequence performance on the same task. Further, our study illustrates the utility of using multiple MR measures and analysis techniques to specify the interpretation of structural findings.